The Effect of Spot Welding Current on Shear Strength in St 40 Steel Plate Joints - Pancarana, I Dewa Made; Suherman, I Ketut (Jurnal Rekayasa Mesin, 2025)
Steel has several classifications, one of which is low carbon steel St 40. Low carbon steel plate St 40 is usually used for industry, machinery, shipping, household appliances and others. Although it is a low carbon steel and relatively easier to weld, St 40 steel still requires attention to the effects of heat. Excessive heating can change the microstructure of steel in the heat affected zone (HAZ), which has an impact on its mechanical properties. Controlling the electric current in the spot welding process greatly affects the characteristics of the welding results, such as the quality of the weld, tensile strength, hardness, area of ​​the HAZ, and the strength of external influences. This study aims to investigate the effect of electric current in the spot welding process on the shear strength of St 40 steel plate material. The method used is an experimental test, in which the spot welding process was carried out nine times on St 40 steel with three variations of input current (20.36A, 24.54A, and 28.95A) and a welding time of 8.0 seconds, using the shear test method according to the AWS D8.9M shear test standard.Based on the research results, it can be seen that the highest average shear strength is 6.72 MPa, which occurs at an input current of 28.95 A with an output current of 6011.47 A, a welding time of 8.0 seconds with a heat input of 88007.92 J and the lowest average shear strength is 1.67 MPa at an input current of 20.36 A with an output current of 6011.47 A, a welding time of 8.0 seconds with a heat input of 61894.30 J. This shows that increasing the electric current increases the shear strength value and vice versa.